Simplified correlations for heat transfer coefficient and heat flux density of radiant ceiling panels. (17th February 2017) - Yuan, Yongli; Zhang, Xu; Zhou, Xiang
Abstract : The radiant ceiling system is considered to be a promising technology capable of meeting sustainable cooling requirements. Correct evaluation of the heat transfer process is important for its design and practical applications. This article reports a research on developing new simplified correlations for the total heat transfer coefficient and total heat flux density of the radiant ceiling panels. The correlations are proposed based on experimental results. The experiments are conducted in a climate chamber under different combinations of indoor operative temperature and supply water temperature. Unlike the existing correlations expressed in literatures, the new correlation for the total heat transfer coefficient takes into consideration both the operative temperature and the supply water temperature. Results show that the calculated total heat transfer coefficients by this correlation differ from the experimental results within ±7%. The new correlation is also extended to total heat flux density based on the inherent relationship between it and the total heat transfer coefficient. Results demonstrate that the predicted difference of the total heat flux density is also smaller than 7%. The results and the method reported in this study could be helpful in practical engineering applications.